HOW STUDENTS SOLVE PIZZA PROBLEMS: AN EXPLORATION OF STUDENTS' MATHEMATICAL LITERACY - Nego Linuhung; Purwanto Purwanto; Sukoriyanto Sukoriyanto; Sudirman Sudirman (Universitas Muhammadiyah Metro, 2023)
The purpose of this study is to describe the mathematical literacy of students in solving pizza problems that have been adapted in the process component and differences. This study focuses on students' answers in solving pizza problems with different information in each question. Data collection was carried out using tests and interviews. In this study, the research method employed is qualitative with a descriptive approach. The research subjects were ninth-grade junior high school students. Data collection was carried out to identify students' mathematical literacy on pizza problems by analyzing the results of tests and interviews. The results showed that: 1. students had difficulty in solving pizza problems, formulating mathematical problems, performing calculations using the concept of specific formula rules, and interpreting from a precise process correctly. The highest level of students' difficulty was observed in the stage of employing the concept of specific formula rules to solve problems; 2. there is a difference in students' answers in solving three types of pizza problems. Besides, students show better performance because they can understand the issues more easily. Therefore, in adapting a question from a foreign language, a careful, thorough, and accurate interpretation is required.